Pendampingan Pelaporan SPT Tahunan PPH Wajib Pajak Orang Pribadi 1770 SS Melalui E-Filing - Pundissing, Rati; Kannapadang, Dwibin; Tangkeallo, Dian Intan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The tax sector is the biggest supporter of state revenue, therefore the reporting of the Annual Income Tax Return for Individual Taxpayers needs to be considered by every taxpayer in an organization, where the obligation as a taxpayer must make a report no later than March 31 of the following year through e-filing. The e-filing system can help employees report their tax obligations to the government more easily and transparently. The purpose of implementing Community Service (PKM) is to help partner employees understand what income tax is and how to use e-filing in reporting the Annual Income Tax Return for Individual Taxpayers 1770 SS. This is done to support employee compliance and responsibility in fulfilling their obligations as taxpayers. The method for implementing this PKM is by providing material, filling out simulations and assisting in reporting the Annual Income Tax Return for Individual Taxpayers 1770 SS via e-filing, so that each employee can report the Annual Income Tax Return directly.